Conducting community-based participatory research in an urban Malaysian community: Lessons learned and challenges in establishing partnerships - Teoh, Gaik Kin; Tan, Maw Pin; Tan, Joo Siang; Chong, Mei Chan (Wiley, 2018)
This paper presents the process of how partnerships are established between an urban residential community and an academic institution in Malaysia by employing community-based participatory research, which involves researchers, community members, and organizational representatives as coresearchers. The research process encompasses colearning, power sharing, and coconstructing of knowledge, with the community members driving the research direction. The research paradigm is grounded on conducting research with the community. This paper highlights the experience and lessons learned while applying the principles of community-based participatory research that promotes social participation of older persons living in a residential community. Two pertinent challenges surface in the research process. The first challenge involves the complexity noted in the gap between the emancipation of community-based participatory research and the hierarchical social structure of the society. The second challenge is the prevalence of unspoken yet subtle domination that undermines the local cultural values affecting the process of coconstructing knowledge with the community. Recommendations for addressing these challenges include future partnerships with other Malaysian communities as well as cross-border research partnerships.